PENGELOLAAN ASSETS PERUSAHAAN DALAM OPTIMALISASI LABA - Juwari Juwari; Ting Anita Salim; Sudjinan Sudjinan (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2021)
The purpose of this research is to find out the extent of the company's financial performance in order to manage the company's assets in achieving optimal profit, the performance of the management of the company's assets can be seen from the Activity Ratio, namely Cash Turnover, Receivables Turnover, and Inventory Turnover, based on the results of analysis both simultaneously and partially to the optimization of profit. The object in this study is PT. Indofood Sukses Makmur, Tbk, while the data used is the financial statements of PT. Indofood Sukses Makmur, Tbk, the first quarter of 2010 – the fourth quarter of 2020. The data analysis method uses multiple linear regressions with classic assumption test, F Test (simultaneous), and t test (partial). Based on the classic Assumption test does not occur multicolerity, autocorrelation and heteresdastisitas. The results of simultaneous analysis (Test F) show that Cash Turnover, Receivable Turnover, and Inventory Turnover have a significant influence.